Regulating blockchain for sustainability? The critical relationship between digital innovation, regulation, and electricity governance. (June 2021) - Amenta, Carlo; Riva Sanseverino, E.; Stagnaro, Carlo
Highlights: Blockchain can prove a disruptive innovation also for energy markets. The presence of a physical asset managed by a utility makes the blockchain application in the sector more reliable. Innovation like blockchain could prove disruptive or incremental for the sector. Blockchain application calls for some regulatory challenges in the sector that have to be properly addressed. Abstract: Blockchain technology has found several innovative applications in the electricity industry. However, its potential has still to be discovered. This is partly due to the role that regulation plays in electricity markets. To be introduced, experimented with, and eventually adopted on a commercial scale, blockchain-supported innovations need to fit the existing regulatory framework or the rules to be reshaped or updated. We focus on energy regulators' possible responses to the blockchain-enhanced market operations (both from the incumbents and potential newcomers), suggesting a monitoring mechanism that can support innovation.